Re-examining Early Warning Systems and Humanitarian Responses in Pastoral Areas of the Northern Kenya and Southern Ethiopia: Initial Findings - Hassan, Rahma (Jameel Observatory for Food Security Early Action, 2024)
Presented at Jameel Observatory for Food Security Early Action Community of Practice meeting, Nairobi, 14-15 May 2024